Traditional Ulama Movement Against Invaders: Darul Uloom Deoband, India and Pesantren Tebuireng, Indonesia - Achmad Zaini (Islamica: Jurnal Studi Keislaman, 2022)
This article attempts to describe the role of ulama (Islamic Scholars) of Darul Uloom Deoband in India and those of Pesantren Tebuireng Jombang in Indonesia, who are categorized as traditionalist, in the independence movement against the invaders. The ulama of Darul Uloom Deoband opposed to the British rule, while the ulama of Tebuireng struggled against the Dutch colonialism and Japanese occupation. Using a historical approach, this article reveals that traditionalist scholars in both institutions had a significant role in the independence movement, even though Islam is minority in India and majority in Indonesia. They fostered anti-colonial attitudes against the invaders in order to defend their homeland and fight for their country’s independence.